2022
DOI: 10.1007/978-3-031-16770-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Deep Gaussian Processes for Angle and Position Discrimination in Active Touch Sensing

Abstract: Active touch sensing can benefit from the representation of uncertainty in order to guide sensing movements and to drive sensing strategies that operate to reduce uncertainty with respect to the task at hand. Here we explore learning approaches that can acquire task knowledge quickly and with relatively small datasets and with the potential to be exploited for active sensing in robots and as models of biological sensory systems. Specifically, we explore the utility of deep (hierarchical) Gaussian Process model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It has been previously demonstrated that linear dimensionality reduction of systematically collected tactile data involving orientation and sensor position produces a structured manifold. The generated manifold reflects regularities from the observational space with the potential to support accurate perception of magnitudes for sensorimotor control [1]; specifically in the discrimination of angle and position of the sensor with respect to the edge of an object using non-parametric models in supervised learning [14]. Alternatively, non-linear dimensionality reduction has been studied in the context of learning a manifold to relate tactile data and actions for object recognition [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that linear dimensionality reduction of systematically collected tactile data involving orientation and sensor position produces a structured manifold. The generated manifold reflects regularities from the observational space with the potential to support accurate perception of magnitudes for sensorimotor control [1]; specifically in the discrimination of angle and position of the sensor with respect to the edge of an object using non-parametric models in supervised learning [14]. Alternatively, non-linear dimensionality reduction has been studied in the context of learning a manifold to relate tactile data and actions for object recognition [17].…”
Section: Introductionmentioning
confidence: 99%